OPTIMIZATION OF SIGNALIZED INTERSECTION PERFORMANCE USING THE IHCM 1997 APPROACH IN AN URBAN INDUSTRIAL AREA: A CASE STUDY OF THE DAM MUKA KUNING INTERSECTION, BATAM - Fauzan (Bulletin of Engineering Science, Technology and Industry, 2026)
Traffic congestion at signalized intersections in urban areas has become a critical issue as transportation activities increase due to economic growth and urbanization. The Dam Muka Kuning intersection in Batam City is one of the strategic intersections located within an industrial zone, characterized by high traffic volumes and significant vehicular movement complexity. This study aims to evaluate the performance of the signalized intersection based on capacity parameters and degree of saturation, as well as to formulate signal timing optimization strategies to improve the intersection's level of service. The method employed is a quantitative approach based on the 1997 Indonesian Highway Capacity Manual (IHCM), utilizing traffic volume data obtained from field surveys during peak hours. The analysis encompasses saturated flow, capacity, flow ratio, and degree of saturation for each intersection approach. The findings indicate that the intersection operates under oversaturated conditions, with degree of saturation (DS) values reaching 3.81 at the south approach, 2.55 at the west approach, and 1.88 at the east approach all of which substantially exceed the ideal threshold (DS ≤ 0.85). These conditions signify a significant deterioration in the level of service, marked by extensive queue lengths and high delays. The predominant factors contributing to congestion include high side friction, ingress and egress activities associated with the industrial zone, and signal timing configurations that have yet to adapt to traffic flow fluctuations. To enhance intersection performance, this study proposes a signal timing optimization strategy based on actual traffic conditions through the adjustment of cycle times and green time distribution. Furthermore, side friction management and geometric improvements at the intersection are necessary to support the effectiveness of traffic engineering measures. The findings of this study offer a practical contribution to the management of signalized intersections in urban areas experiencing high levels of saturation.